(untitled) (Journal of Energy and Safety Technology (JEST), 2024)
As solar photovoltaic technology becomes more affordable globally, Stand-Alone Photovoltaic (SAPV) systems are being recognized as a viable solution for powering essential services in areas lacking grid connectivity. The paper begins with a comprehensive review of SAPV systems, highlighting their categorization, benefits, and typical applications, especially in remote areas. Subsequently, it delves into the design and sizing aspects of these systems, emphasizing the importance of choosing appropriate components, including PV modules, batteries, charge controllers, inverters, and cables. A detailed methodology outlines the intuitive design process, incorporating factors like site selection, solar potential assessment, daily energy needs calculation, and component sizing. This systematic yet straightforward methodology bridges the gap between theoretical design principles and practical implementation. To demonstrate the applicability of the proposed approach, a case study is included, offering real-world insights and best practices for SAPV system deployment. This study contributes to the field of renewable energy by addressing specific challenges associated with SAPV system design in off-grid areas, such as the need for accurate solar irradiation data and precise component sizing. By providing a structured framework and practical guidance, this work serves as a valuable reference for researchers, engineers, and policymakers aiming to optimize SAPV systems for sustainable development and to enhance energy access in remote regions.